Intra- and Postoperative Electrocochleography May Be Predictive of Final Electrode Position and Postoperative Hearing Preservation - O'Connell, Brendan P.; Holder, Jourdan T.; Dwyer, Robert T.; Gifford, René H.; Noble, Jack H.; Bennett, Marc L.; Rivas, Alejandro; Wanna, George B.; Haynes, David S.; Labadie, Robert F. (Frontiers in Neuroscience, 2017)
Introduction: The objectives of the current study were to 1) determine the relationship between electrocochleography (ECochG), measured from the cochlear implant (CI) electrode array during and after implantation, and postoperative audiometric thresholds, 2) determine the relationship between ECochG amplitude and electrode scalar location determined by computerized tomography (CT); and 3) determine whether changes in cochlear microphonic (CM) amplitude during electrode insertion were associated with postoperative hearing. Materials & Methods: Eighteen subjects undergoing CI with an Advanced Bionics Mid-Scala device were prospectively studied. ECochG responses were recorded using the implant coupled to a custom signal recording unit. ECochG amplitude collected intraoperatively concurrent with CI insertion and at activation was compared with audiometric thresholds postoperatively. Sixteen patients also underwent postoperative CT to determine scalar location and the relationship to ECochG measures and residual hearing. Results: Mean low-frequency pure tone average (LFPTA) increased following surgery by an average of 28 dB (range 8-50). Threshold elevation was significantly greater for electrodes with transcalar dislocation. No correlation was found between intraoperative ECochG and postoperative behavioral thresholds collapsed across frequency; however, mean differences in thresholds measured by intraoperative ECochG and postoperative audiometry were significantly smaller for electrodes inserted completely within scala tympani (ST) versus those translocating from ST to scala vestibuli. A significant correlation was observed between postoperative ECochG thresholds and behavioral thresholds obtained at activation. Discussion: Postoperative audiometry currently serves as a marker for intracochlear trauma though thresholds are not obtained until device activation or later. When measured at the same time-point postoperatively, low-frequency ECochG thresholds correlated with behavioral thresholds. Intraoperative ECochG thresholds, however, did not correlate significantly with postoperative behavioral thresholds suggesting that changes in cochlear physiology occur between electrode insertion and activation. ECochG may hold clinical utility providing surgeons with feedback regarding insertion trauma due to scalar translocation, which may be predictive of postoperative hearing preservation. Conclusion: CI insertion trauma is generally not confirmed until postoperative audiometry when loss of residual hearing is confirmed. ECochG has potential to provide estimates of trauma during insertion as well as reliable information regarding degree of hearing preservation.